Analysis of Metacognition Knowledge Post Problem Based-Blended Learning (PBBL) Hydrolysis-Buffer Material Implementation - Ningrum, Puji; Haryani, Sri; Wijayati, Nanik (Journal of Innovative Science Education, 2020)
Metacognition knowledge is needed in the problem solving process. This knowledge has not been much taught and practiced to students. The research intends to provide information about (1) the profile of students' metacognition knowledge, (2) relationships, and (3) the contribution of metacognition knowledge to cognitive learning outcomes. The research subjects were 143 students of class XI SMAN 10 Semarang with research design of mixed method-sequential explanatory. Written test as a source of quantitative data and the Metacognitive Activities Inventory (MAI-1) questionnaire as a source of qualitative data. The metacognition knowledge of students is on the criteria of "ok". The relationship with cognitive learning outcomes obtained from the product moment correlation test results, r = 0.983 and the correlation coefficient significance test, Fh = 4041,84. The conclusion, there is a relationship between metacognition knowledge on cognitive learning outcomes. Contributions to cognitive learning outcomes are very high, amounting to 96.63%. PBBL is effective in empowering and training metacognition knowledge in the learning process in the classroom.